Conversation Principles: Study of Surah Al-Anbiya' Paragraph 89, 87, 85 and 83 - Mukhamad Syaiful Milal (CMES (Center of Middle Eastern Studies), 2022)
This research aims to disclose and dismantle principles of conversation in Surah Al-Anbiya' verses 89, 87, 83 and 85 with a pragmatic approach. The verse was chosen because it represents a pragmatic phenomenon that draws further attention from the point of view of this study. The research will focus on analyzing the content and meaning contained in the verse which is then interpreted with the principle of cooperation between the speaker and the speech partner. The theory of conversational principles in this study is the theory proposed by Grice in 1975, covering the maxims of quantity, quality, relationship and implementation with various forms of violation or non-compliance with these maxims. Al-Quran is Allah SWT in the form of text and timeless, so that the study in the Al-Quran will present various interpretations that will become his word. In Surah al-Anbiya 'Recounts the conversation between creatures and God. In this verse and in practice, conversations between lovers of Allah SWT as speech partners contain several pragmatic phenomena with the principles of conversation between the parties involved. The implementation of these conversational principles has their respective duties and functions based on the situation of the speech act. However, in this communication, is four maxims are not always implemented.